Effect of water on the thermal transition in chitosan films. (11th November 2019) - Qiao, Congde; Ma, Xianguang; Wang, Xujie; Yao, Jinshui
Abstract: In this study, the influence of moisture content on the thermal behavior of chitosan was investigated by differential scanning calorimetry (DSC). An endothermic peak at around 100°C was generally observed for hydrated chitosan films. This endothermic event was attributed to the melting transition of chitosan in pans with good seal integrity, whereas it was assigned to the evaporation of water from sample in an open system. The melting temperature ( T m ) of chitosan was closely related to the water content. At low water contents up to 27 wt%, the T m increased with increasing hydration level. At moderate water contents up to 135%, T m decreased with further increasing water content. At high water contents superior to 135%, the melting transition was no longer visible in the DSC thermogram. In addition, the T m of chitosan in alcohol‐aqueous mixed solvents increased with an increase in 1‐propanol concentration. The addition of urea could significantly increase the T m of chitosan at high hydration levels, whereas it was independent on urea content for less hydrated samples. These observations indicate that the role of water is complex, depending on its state in polymer matrix. Abstract : In this work, the influence of moisture content on the thermal behavior of chitosan was investigated. It was found that the integrity of the seal of the differential scanning calorimetry pans, as well as the hydration level, plays an important role in the melting behavior of biopolymers. These results suggest that the role of water is complex depending on its state in the polymer matrix.